Building Psychological Resilience in Military Personnel: Theory and Practice. 2013
DOI: 10.1037/14190-005
|View full text |Cite
|
Sign up to set email alerts
|

The role of transformational and ethical leadership in building and maintaining resilience.

Abstract: As discussed in more detail by other authors in this volume, resilience is often defined as the ability to adapt to or bounce back from threatening situations and refrain from engaging in maladaptive behavior. According to van Breda (2011), resilience, "along with assets, strengths, and solutions, has become an increasingly mainstream concept in recent years" (p. 33). if we accept that stressors can have extremely adverse consequences and understand that resilience provides people with the capacity to deal eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Especially, the moral characteristics of an ethical leader improve the mental health of employees, thereby improving their resilience (β = 0.28). Our results are in line with previous researchers who indicated that ethical leaders could influence the resilience of their followers by building respect, consistency and trust which then influences their resilience (MacIntyre et al, 2013b ). From a leadership standpoint, a leader helps employees to build a higher level of resilience by promoting employees' mindfulness and personal resilience plans (Sommer et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Especially, the moral characteristics of an ethical leader improve the mental health of employees, thereby improving their resilience (β = 0.28). Our results are in line with previous researchers who indicated that ethical leaders could influence the resilience of their followers by building respect, consistency and trust which then influences their resilience (MacIntyre et al, 2013b ). From a leadership standpoint, a leader helps employees to build a higher level of resilience by promoting employees' mindfulness and personal resilience plans (Sommer et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moon and Jung ( 2018 ) indicated that the moral character of a corporate leader focuses on fostering employees' mental health through a positive and healthy work environment. MacIntyre et al ( 2013b ) believed that ethical leaders can influence the resilience of their followers by building respect, consistency and trust, which then influences their resilience.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the leader can influence followers through daily interactions, such as allocating resources, providing feedback, and evaluating performance (Volmer, 2012). Limited but insightful research has confirmed that certain leadership styles can improve followers' resilience (Ahern, 2015;Maclntyre et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The findings provide empirical support for most of the proposed hypotheses. The first hypothesis addresses the point raised by Luthans and Avolio (2003) that the influence of leadership on resilience has been overlooked in the literature, as there are only a handful of studies that suggest that transformational and RL behavior increases subordinate resilience (Harland et al, 2004;Higgs, 2003;MacIntyre et al, 2013). Our first set of findings showed that RL was positively associated with FR (H1), both as a whole and in terms of SN and SC components within the UAE.…”
Section: Discussionmentioning
confidence: 81%